Implementation of the Strategy for Memorizing Arabic Vocabulary with the Hanifida Method - Ahmad Rouyani Al Bahroni; Muhammad Arif Setia Budi (Institut Dirosat Islamiyah Al-Amien Prenduan, 2023)
Arabic is one of the foreign languages developed in educational institutions in Indonesia, especially in Islamic boarding schools and educational institutions with Islamic characteristics, even in government schools that have language majors. Ahmed Fuad Effendi said,